Productivity trends and income inequality in Latvia - Baranova, Daira; Baranovs, Olegs; Skribane, Irina (University of Latvia, 2020)
Increasing labour productivity is a key driver for prosperity. Although Latvia's productivity growth rates are among the highest in the EU, productivity growth has declined in recent years. With the productivity dynamics slowing down, the pace of convergence is also slower. The benefits of the recent economic recovery in Latvia have not been evenly distributed among households and income inequality has not diminished significantly. The recent OECD and academic studies point to a correlation between falling productivity and increasing income inequality. The more unequal a society is, the more it affects productivity growth and the sustainability of growth. Improving productivity has the potential to affect inequalities in a positive and negative way. To find suitable policy answers therefore is extremely challenging. The research describes the dynamics of productivity and income inequality, their interaction in Latvia. The research is based on existing data, studies, and policy documents. It aims to integrate the available data from a broad range of international and domestic sources from the perspective of Latvia. The research argues that easy gains from catching up are over, keeping productivity dynamic will not be easy, as the factors that provided relatively high productivity rates in previous periods are likely to be exhausted and companies are approaching the limits of existing technology. Continued progress in implementing structural reforms will be needed to reduce the productivity gap, only systemic implementation of all policies and structural reforms can provide a desirable outcome. In order to reduce income inequality, it is important to strengthen the competitiveness of the regions of Latvia and to improve the tax and benefit system.
Keywords: productivity; income inequality; economic policy; Research Subject Categories::SOCIAL SCIENCES::Business and economics